Menstrual Disorders Related to Eating Disorders - Milano, Walter; Ambrosio, Paola; Carizzone, Francesca; De Biasio, Valeria; Foia, Maria G.; Saetta, Biancamaria; Milano, Maria Francesca; Capasso, Anna (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Eating Disorders (ED) are associated with multiple physical complications that strongly affect the physical health of these young and fragile patients and can also cause significant mortality, the highest among psychiatric pathologies. Among the various organic complications, albeit still little known, the gynecological implications, up to infertility, are very widespread. Both among adolescent and adult patients, gynecological symptoms can be very widespread and range from menstrual irregularities to amenorrhea, from vaginitis to ovarian polycystosis, up to complications during the gestational phase and in postpartum, in addition to the possible consequences on the unborn child. Among the most frequent and significant gynecological disorders in women with ED, there are menstrual irregularities that may occur with oligomenorrhea or even amenorrhea. This symptom, although no longer part of the DSM-5 diagnostic criteria for defining Anorexia Nervosa (AN), must be considered a very relevant event in the overall evaluation of young women and adolescents with eating disorders. Functional Hypothalamic Amenorrhea in ED patients is related to psychological distress, excessive exercise, disordered eating, or a combination of these factors which results in suppression of the hypothalamic- pituitary-ovarian axis, resulting in hypoestrogenism. The objective of this paper is to summarize the causes and the mechanism underlying the menstrual disorders and to provide a better understanding of the correlation between the reproductive system and the mechanisms that regulate food intake and eating habits. In addition, early recognition of risk factors for eating disorders for gynecological implications can help put more accurate assessments of patients to prevent potentially fatal complications. The importance of the involvement of specialist gynecologists in the multidisciplinary team that has to follow patients with eating disorders is also discussed.
Keywords: Menstrual Cycle